2016
DOI: 10.1016/j.cell.2016.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics Controls T Cell Fate through Metabolic Programming

Abstract: SUMMARY Activated effector T (TE) cells augment anabolic pathways of metabolism, such as aerobic glycolysis, while memory T (TM) cells engage catabolic pathways, like fatty acid oxidation (FAO). However, signals that drive these differences remain unclear. Mitochondria are metabolic organelles that actively transform their ultrastructure. Therefore, we questioned whether mitochondrial dynamics controls T cell metabolism. We show that TE cells have punctate mitochondria, while TM cells maintain fused networks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,033
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,125 publications
(1,142 citation statements)
references
References 64 publications
57
1,033
3
3
Order By: Relevance
“…As regards the anti-tumor T cell response, forcing mitochondrial fusion during in vitro T cell expansion promotes differentiation of naïve T cells toward a memory phenotype, as recently demonstrated [202]. This can confer a higher survival to these cells during ACI.…”
Section: Targeting Mitochondrial Dynamics To Improve the Anti-cancermentioning
confidence: 82%
See 2 more Smart Citations
“…As regards the anti-tumor T cell response, forcing mitochondrial fusion during in vitro T cell expansion promotes differentiation of naïve T cells toward a memory phenotype, as recently demonstrated [202]. This can confer a higher survival to these cells during ACI.…”
Section: Targeting Mitochondrial Dynamics To Improve the Anti-cancermentioning
confidence: 82%
“…By contrast, memory T cells (T M ) switch towards fatty-acid oxidation to sustain their metabolism and self-renewal, thus increasing their mitochondrial mass and sparing respiratory capacity (SRC) [201][202][203][204]. It has been recently shown that Opa-1 activity is essential to allow the correct formation and survival of T M cells, in which the mitochondrial network is clearly more elongated than in T E cells [202]. Pharmacological modulation of mitochondria-shaping proteins during in vitro T cell expansion, forcing mitochondria towards fusion, leads to the acquisition of a memory-like phenotype and to an increased survival rate, thus rendering T cells more effective in reducing tumor growth during adoptive cell immunotherapy (ACI) (Fig.…”
Section: Cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites such as succinate and citrate have a direct effect on the functioning of immune cells such as macrophages and dendritic cells [106]. Mitochondrial dynamics has been implicated as a major determinant in T-cell fate [107]. BMAL1 and the molecular clock are major players in immunity, metabolic reprogramming and mitochondrial homeostasis.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%
“…Investigation of mitochondrial morphology demonstrated that memory T cells have fused mitochondria while effector T cells have fissed mitochondria. Fusion protein Opa1 is required for memory T cells [10].…”
Section: Lymphocytesmentioning
confidence: 99%